METHODS FOR OBTAINING SILVER NANOPARTICLES - A REVIEW. (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Silver has been part of active medical use for treatment and disinfection from ages, even in the present times. Particularly relevant today is the question of the effect of silver nanoparticles on bacteria and viruses, including against COVID-19. The study reviews distinct methods for producing silver nanoparticles. The comparison and preferences of different methods based on their classification and features are reviewed. The main goal of this study is to reveal the top-notch method and their benefits and prospects of the possibilities of the method - laser ablation, as a cost-effective and environment friendly technology for generating silver nanoparticles in an aqueous environment. The method of Pulsed Laser Ablation in Liquid for obtaining nanoparticles is explained in detail. The paper is divided into several main parts, starting with a briefing on silver and its nanoparticles and is followed by various methods for their production.